FEATURES OF TESTING OF INERTIALLY STABILIZED PLATFORMS - Sushchenko, Olha (Proceedings of National Aviation University, 2018)
Purpose: the paper focuses on problems of testing of inertially stabilized platforms operated on ground vehicles. The main goal is to consider possibilities to test such systems using simulation. Methods: to solve the given problem methods of inertilal stabilization, creation of mathematical models and simulation are used. MatLab possibilities are taken into consideration. Results: testing of basic accuracy characteristics by means of simulation is considered. The appropriate mathematical models are developed. Presence of different modes during functioning inertially stabilized platforms is taken into consideration. The approaches to estimation of static and dynamic errors are given. The ways to set tested signals taking into consideration features of testing bench are considered. The possibility to estimate angular rigidity by the moment is proposed. Conclusions: the results of simulation of different tested signals are represented. Proposed ways to estimation of operating characteristics of inertially stabilized platforms allow decrease time and cost losses of testing. Obtained results can be useful for design of inertially stabilized platforms for vehicles of the wide class.